2023
DOI: 10.1186/s12974-023-02875-x
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 regulates iron-dependent hippocampal synapses and functional connectivity damage in depression

Ting Zeng,
Junjie Li,
Lingpeng Xie
et al.

Abstract: Neuronal iron overload contributes to synaptic damage and neuropsychiatric disorders. However, the molecular mechanisms underlying iron deposition in depression remain largely unexplored. Our study aims to investigate how nuclear factor-erythroid 2 (NF-E2)-related factor 2 (Nrf2) ameliorates hippocampal synaptic dysfunction and reduces brain functional connectivity (FC) associated with excessive iron in depression. We treated mice with chronic unpredictable mild stress (CUMS) with the iron chelator deferoxamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Secondly, we believe that the difference of stress mode and time is also an important reason affecting the experimental results. 25 Moreover, we also found inhaling BEO increased dendritic length and spine density in the HIPP of CUMS-induced rats.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Secondly, we believe that the difference of stress mode and time is also an important reason affecting the experimental results. 25 Moreover, we also found inhaling BEO increased dendritic length and spine density in the HIPP of CUMS-induced rats.…”
Section: Discussionsupporting
confidence: 51%
“…This is similar to the results of some studies in recent years, CUMS induced the decrease of dendrite length and spinal density in the brain region of depressed rats. 6,[22][23][24][25] Hei et al found that chronic mild stress increased the density of synpase and small spine in inner and outer in DG, 26 which may be strongly related to different types of animal models, because our research object is rats, while Hei et al's research object is mice.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated higher expression levels of TF and TfR1 in the peripheral blood and brain of CSDS-induced depression mouse models compared to the control group ( CHANG et al, 2022 ). Further studies have demonstrated a strong correlation between the onset of depression and the reduction of hippocampal neuronal synapses, which is attributed to the upregulation of TfR1 and downregulation of FTL caused by nuclear factor erythroid-2 related factor 2 (Nrf2) deficiency ( ZENG et al, 2023 ). These findings align with the research conducted by Wang et al, whose team elucidated the association between iron deposition in the hippocampus and depression, along with confirming the reduction of FTH induced by lipopolysaccharide (LPS) in depressed mice ( WANG et al, 2021a ).…”
Section: Depression and Ferroptosismentioning
confidence: 99%
“…Neuroinflammation refers to the immune response of the central nervous system (CNS) mediated mainly by microglia and astrocytes in the hippocampus ( LEE and HYUN, 2023 ). Microglia, known for their high iron content ( UZUNGIL et al, 2022 ), have been implicated in depression associated with abnormal glial activation and iron overload, suggesting a potential connection between iron and neuroinflammation ( ZENG et al, 2023 ). However, the precise mechanism by which iron overload disrupts neurotransmitter homeostasis and induces anxiety and depressive behaviors remains unclear ( UZUNGIL et al, 2022 ).…”
Section: Depression and Ferroptosismentioning
confidence: 99%
See 1 more Smart Citation